Preparation of ferulic acid-grafted chitosan using recombinant bacterial laccase and its application in mango preservation. Issue 13 (12th February 2018) - Yang, Jie; Sun, Jianna; An, Xiujuan; Zheng, Meixia; Lu, Zhaoxin; Lu, Fengxia; Zhang, Chong
Abstract : To improve the antioxidant and antibacterial properties of chitosan, recombinant bacterial laccase from Bacillus vallismortis fmb-103 (fmb-rL103) was used to catalyze ferulic acid grafting. Abstract : To improve the antioxidant and antibacterial properties of chitosan, recombinant bacterial laccase from Bacillus vallismortis fmb-103 (fmb-rL103) was used to catalyze ferulic acid grafting. The grafted chitosan was characterized using UV-vis and FT-IR techniques. DPPH free radical scavenging results indicated that the antioxidant properties of the grafted chitosan (FA- g -CS) were significantly improved. Meanwhile, the antibacterial properties against E. coli, S. aureus, B. subtilis, and M. guilliermondii were also improved. Furthermore, FA- g -CS was applied to mango preservation as a coating, which improved the sensory qualities of mango Mangifera indica L. The disease incidence of mangoes coated with FA-grafted medium and high molecular weight chitosan were 0 and 5%, respectively. The respiratory peak was delayed more than 4 days, and the titratable acidity and ascorbic acid concentration were all enhanced. POD and CAT activities in FA- g -CS coated mangoes were higher than those coated with chitosan samples with a lower H2 O2 concentration.